Gastrointestinal-associated autoantibodies in different autoimmune diseases (2012)
Background: Gastrointestinal (GI)-related autoantibodies (Abs) are rarely evaluated in autoimmune diseases (AID) other than inflammatory bowel disease, autoimmune hepatitis and celiac disease. Our aim was to determine the prevalence of these antibodies in a wide spectrum of AID. Methods: We examined 923 serum samples representing 18 AID and compared them with 338 samples from healthy subjects. We used the BioPlex 2200-immunoassay (Bio-Rad, USA) to test samples for the presence of IgA and IgG directed at gliadin (AGA), tissue-transglutaminase (tTG), and Saccharomyces cerevisiae (ASCA). Results: Prevalence of IgA AGA was significantly higher in antiphospholipid syndrome (APS) (7.1 %, P=0.012) and in pemphigus vulgaris (25%, P =0.008) patients, as compared with healthy controls. Presence of IgG-AGA was more common among Crohn’s disease (20.5%, P = 0.023) and rheumatoid arthritis (6.5%, P=0.027) patients. IgG anti tTG were frequently observed in APS (6.1%, P=0.012), in giant cell arteritis (11.5%, P=0.013) and in ulcerative colitis (11.1%, P=0.018) patients, and as expected, higher prevalence of ASCA (IgA 19.3% and IgG 27.7%) was found in Crohn’s disease. IgG ASCA were also found in systemic lupus erythematosus (SLE) (4.5%, P=0.01), in Graves’ disease (5.7%, P=0.018), in cryoglobulinemia (7.1%, P=0.006), and in patients with vasculitides (6.5%, P=0.002). In contrast, lower prevalence of IgG type AGA was found in SLE (P=0.034), cryoglobulinemia (P=0.019) and vasculitides (P=0.013) patients. Conclusions: Our findings suggest an association between GI-related- Abs and a wide spectrum of AID. The clinical implication of these findings is yet to be determined.